Curricular trends in the Universidad Francisco de Paula Santander academic program offerings (2019)
The objective of the research work, was to analyze the curriculum of the programs from "Universidad Francisco de Paula Santander" in San José de Cucuta, Colombia. The sample was participatory non-probability, with the participation of 200 students from Catatumbo and university student's, both from the different semesters and documents curriculums. A mixed study of sequential explanatory design was applied. In the first quantitative phase, the results were obtained by applying a digital questionnaire to the students. The data were analyzed using the observation guide for their respective analysis. The results of both phases were merged by the contrasting method. The conclusions demonstrate the importance of curriculum for training in research and innovation and critical thinking, curriculum for the creation, adaptation and/or use of communication and information technologies, curriculum for social inclusion in the university.